Longitudinal Analysis of Immigrant Occupational Mobility: A Test of the Immigrant Assimilation Hypothesis - Barry R. Chiswick; Yew Liang Lee; Paul W. Miller (Institute for the Study of Labor (IZA), 2002)
Using an immigrant assimilation framework, this paper develops a model of the occupational mobility of immigrants and tests the hypotheses using data on adult males from the Longitudinal Survey of Immigrants to Australia. The theoretical model generates hypotheses regarding a U-shaped pattern of occupational mobility from the ?last job? in the origin, to the ?first job? in the destination, to subsequent jobs in the destination, and regarding the depth of the ?U.? The survey includes data on pre-immigration occupation, the ?first? occupation in Australia (at 6 months) and the occupation after about 3.5 years in Australia. The hypotheses are supported by the empirical analysis.
Keywords: J24; J61; J62; J15; 330; Immigrants; occupational mobility/attainment; assimilation; longitudinal data; Australia; Migranten; Arbeitsmobilität; Soziale Integration; Schätzung; Australien